Changes in BMI-distribution from 1966-69 to 1995-97 in adolescents. The Young-HUNT study, Norway - Mykletun Arnstein; Lydersen Stian; Bjørnelv Sigrid; Holmen Turid Lingaas (BMC, 2007)
Abstract Background The aim of this study was to explore changes in the BMI-distribution over time among Norwegian adolescents. Methods Height and weight were measured in standardised ways and BMI computed in 6774 adolescents 14-18 years who participated in the Young-HUNT study, the youth part of the Health-study of Nord-Trondelag County, Norway in 1995-97. The results were compared to data from 8378 adolescents, in the same age group and living in the same geographical region, collected by the National Health Screening Service in 1966-69. Results From 1966-69 to 1995-97 there was an increased dispersion and a two-sided change in the BMI-distribution. Mean BMI did not increase in girls aged 14-17, but increased significantly in 18 year old girls and in boys of all ages. In both sexes and all ages there was a significant increase in the upper percentiles, but also a trend towards a decrease in the lowest percentiles. Height and weight increased significantly in both sexes and all ages. Conclusion The increased dispersion of the BMI-distribution with a substantial increase in upper BMI-percentiles followed the same pattern seen in other European countries and the United States. The lack of increase in mean BMI among girls, and the decrease in the lowest percentiles has not been acknowledged in previous studies, and may call for attention.